Pelatihan Penulisan Jurnal Ilmiah di Pondok Pesantren Imam Syafi’i Brebes - M. Masrukhan; Mirza Anindya Pangestika (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The scientific journal writing training held at the Imam Syafi'i Islamic Boarding School in Brebes is part of a strategic effort to improve academic literacy and scientific writing skills among students and teaching staff. The background to this activity is the low ability and confidence in scientific writing, which has resulted in minimal involvement of students in academic publications, both at the local and national levels. This training activity involved 30 participants, consisting of final-year students and teachers, using an approach that integrates theory and practice in a balanced manner. The material presented included understanding the structure of scientific journal writing, citation techniques using reference applications, publication ethics, and direct practice in drafting scientific articles. The training was conducted in several intensive sessions, followed by evaluations through pre- and post-tests. The evaluation results showed a significant increase in participants' understanding, where the average score increased from 55 to 80. Not only from a cognitive perspective, participants also showed increased confidence in expressing ideas and systematically compiling scientific writing. Some participants were even able to produce article manuscripts worthy of submission to scientific journals. Although this activity faced several challenges, such as limited training time and access to the latest scientific literature, overall, the training was deemed successful in fostering a stronger academic culture within the Islamic boarding school environment. It is hoped that this training program can be continued and developed sustainably as part of a strategy to strengthen academic capacity and scientific literacy within Islamic boarding schools.